The age of reform (1250-1550) : an intellectual and religious history of late medieval and Reformation Europe - Ozment, Steven E. (Yale University Press, 1980)
The seeds of the swift and sweeping religious movement that turned great numbers of Europeans into Protestants in the early 1500s had been sown far back in the late Middle Ages. In this book, Steven Ozment traces the growth anddispersalof dissenting ideologies through threecenturies to their explosive burgeoning in the 1500s. He elucidates with great clarity the complex philosophical and theological issues that inspired antagonistic schools, traditions, and movements from Aquinas to Calvin.